Career advancement of Filipino graduates and the relationship to their previous student leadership roles. [article]. - Castro, Rosalyn A.
There were five hypotheses:(1) Filipino graduates with previous student leadership roles progress more successfully and faster in their careers than those without previous student leadership roles; (2)Male Filipino graduates progress more successfully in their careers than female Filipino graduates; (3)Filipino graduates in the government offices are more task-oriented than those in the non-governmental organizations and the corporate sector; (4)Filipino graduates experience more personal stress as they progress in their jobs; and (5)Filipino graduates who work in the corporate sector experience more personal stress than those who work in the non-governmental organizations and governmental offices. The respondents for the present study were 156 Filipino graduates (57 males and 99 females), ages 25 above, who have been working in selected non-governmental organizations, government offices or business corporations within Metro Manila for more than five years at the time of the study. Using the independent group samples t-test and chi-square test, only the first hypothesis was significant.